Telerheumatology Origins, Current Practice, and Future Directions - Peoples, Christine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book details the practice of telerheumatology. Telemedicine is defined as the delivery of healthcare and the exchange of healthcare information across distances. Following, telerheumatology is the delivery of rheumatology care through telemedicine. There exists an increasing demand from patients, caregivers, and healthcare systems for access to academic specialists through telemedicine. This has been the case for the past several years and the demand has only increased with the ongoing COVID-19 pandemic. There is currently a lack of rheumatologists in rural areas and that is expected to spread to a general lack by 2025. Telerheumatology offers an excellent and timely solution to fill these gaps and provide care Telerheumatology care has been shown to be feasible and quite effective. The current COVID-19 pandemic has thrust the concept of telemedicine into the spotlight. However, not all telerheumatology care is the same and there exists many nuances and differences when examining telerheumatology care across the United States and the world. After comprehensively reviewing the origins of telerheumatology, this work defines in detail the current practice of telerheumatology, along with the specific impact of the COVID-19 pandemic and all applications of telerheumatology. Expert authors also provide a detailed roadmap for providers to initiate, sustain, and grow a telerheumatology program. The book concludes by covering future directions of telerheumatology, including areas for expansion, improvement, and innovation. After reading this work, the editor and all the contributing authors hope that it will inspire, provoke thought and discussion, and lead to increased adaptation of providing telerheumatology care by rheumatologists and rheumatology providers.
INTRODUCTION -- Telerheumatology: A Historical Perspective -- Overview of Synchronous and Asynchronous Modalities -- The Role of eConsults -- Equipment, Technology, and Support -- Telepresenter Training and the Virtual Physical Exam -- Documentation, Licensing, and HIPAA Compliance -- Legal and Regulatory Primer for the Practice of Telemedicine in the United States -- Best Practices for Billing and Coding -- Determining the Value of Telerheumatology -- MEASURING DISEASE ACTIVITY AND FUNCTIONAL CAPACITY IN TELERHEUMATOLOGY -- Rheumatology Telementoring: The ECHO Model -- Rural Health Care and Telerheumatology -- TELERHEUMATOLOGY AND THE CHRONIC CARE MODEL -- Telerheumatology and the Department of Veterans Affairs -- Review of the Evidence for Telerheumatology -- Satisfaction with Telerheumatology Care: Patient and Clinician Perspectives -- Telerheumatology During the COVID-19 Pandemic and Beyond -- Private Practice and Telerheumatology -- Pediatric Telerheumatology -- Telerheumatology With Learners -- PATIENT PERSPECTIVES AND NARRATIVES -- Future Directions and Innovation.
Keywords: Rheumatology; Rheumatology; Rheumatology -- methods; Telemedicine -- methods